A Brief Review: Advancement in the Synthesis of Amine through the Leuckart Reaction - Qasim Umar; Mei Luo (Reactions, 2023)
This review presents a summary of reactions that take place during the “Leuckart-type reaction”. The significance of, as well as recent advancements in, the synthesis of amines through simple and inexpensive methods using readily available raw materials is discussed. This review includes all catalytic and noncatalytic reactions that involve the Leuckart method. Recent studies have shown that at least a quarter of C–N bond-forming reactions in the pharmaceutical industry are occur with the support of reductive amination. Recently, experimental conditions have achieved excellent yields. The “Leuckart-type reaction” is technically associated with Eschweiler–Clarke methylation. Compounds are grouped in accordance with the precept of action. This includes drugs affecting the central nervous system, cardiovascular system and gastrointestinal tract; anticancer drugs, antibiotics, antiviral and antifungal drugs; drugs affecting anxiety; convulsant, biotic, and HIV drugs; and antidiabetic drugs. Therefore, this review supports the development of the Leuckart-type preparation of nitrogenous compounds, as well as their advancement in other areas of human development.